Synthesis, characterization and corrosion inhibition studies of novel 8-hydroxyquinoline derivatives on the acidic corrosion of mild steel: Experimental and computational studies. (June 2018) - Rbaa, M.; Lgaz, H.; El Kacimi, Y.; Lakhrissi, B.; Bentiss, F.; Zarrouk, A.
Graphical abstract: Abstract: Two newly substituted 8-Hydroxyquinoline derivatives, namely 5-((2-(4-bromophenyl)-5, 6-dimethyl-1H-benzimidazol-1-yl) methyl) quinolin-8-ol (BQM) and 5-((2-(4-bromophenyl)-1H-benzimidazol-1-yl) methyl) quinolin-8-ol (BQ) were synthesized and identified by elemental analysis, IR, 1 H NMR and 13 C NMR spectroscopy. The corrosion inhibition of BQM and BQ in molar hydrochloric acid for mild steel was evaluated using weight loss and electrochemical techniques. It is found also that the inhibition efficiency of these compounds slight decreases with temperature. Both inhibitors adsorption onto the steel surface was found to follow the Langmuir model. Additionally, DFT calculations and Molecular Dynamic simulations (MD) help to gain like wiser insight about corrosion fact.